2016
DOI: 10.1186/s12859-016-1160-0
|View full text |Cite
|
Sign up to set email alerts
|

TopoICSim: a new semantic similarity measure based on gene ontology

Abstract: BackgroundThe Gene Ontology (GO) is a dynamic, controlled vocabulary that describes the cellular function of genes and proteins according to tree major categories: biological process, molecular function and cellular component. It has become widely used in many bioinformatics applications for annotating genes and measuring their semantic similarity, rather than their sequence similarity. Generally speaking, semantic similarity measures involve the GO tree topology, information content of GO terms, or a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…Related applications exist for measuring semantic similarity and are used for the mapping of correspondences and the matching of similarities between concepts of different ontologies (see, e.g. Noy et al., ; Zhang and Bodenreider, ,b; Parmentier et al., ; Travillian et al., ; Bertone et al., ; see also Hoehndorf et al., ; for instance matching see also Shao et al., ; see also Topological Information Content Similarity , Ehsani and Drabløs, ; but see also ontology‐driven approach for analysing molecular networks, Landeghem et al., ). The result of this initial step is the identification of units of comparison (= comparative homologues , Vogt, ) across the semantic instance anatomies of all sister taxa for a given possible tree, which is documented in a consensus comparison graph .…”
Section: Basic Principles For a Graph‐based Methods Of Numerical Tree mentioning
confidence: 99%
See 1 more Smart Citation
“…Related applications exist for measuring semantic similarity and are used for the mapping of correspondences and the matching of similarities between concepts of different ontologies (see, e.g. Noy et al., ; Zhang and Bodenreider, ,b; Parmentier et al., ; Travillian et al., ; Bertone et al., ; see also Hoehndorf et al., ; for instance matching see also Shao et al., ; see also Topological Information Content Similarity , Ehsani and Drabløs, ; but see also ontology‐driven approach for analysing molecular networks, Landeghem et al., ). The result of this initial step is the identification of units of comparison (= comparative homologues , Vogt, ) across the semantic instance anatomies of all sister taxa for a given possible tree, which is documented in a consensus comparison graph .…”
Section: Basic Principles For a Graph‐based Methods Of Numerical Tree mentioning
confidence: 99%
“…Ontology-based annotations of morphological 2D and 3D images could be utilized as another data source (e.g. Dadzie and Burger, 2005;Larson and Martone, 2009;Eliceiri et al, 2012), which could not only significantly contribute to the size of the available data, but also contribute valuable image references for documentation, which subsequently can be used for visualizing the results of the numerical tree inference step (cf. Kuß et al, 2008).…”
mentioning
confidence: 99%
“…The third approach combine the node-and edge-based approaches. Essentially, this hybrid approach considers both the information contained in the nodes and the structure of the GO graph using path distance as weight (Chen et al (2007), Wu et al (2013), Ehsani & Drabløs (2016)), in order to minimize the problem found in edgeand nod-based approach alone.…”
Section: 4mentioning
confidence: 99%
“…TopoICSim (Ehsani & Drabløs (2016)) is a hybrid-based similiraty measure which uses both IC and topology of GO terms in measuring term similarity. First it calculates the weighted distance between two terms.…”
Section: Related Workmentioning
confidence: 99%
“…Semantic similarity measures the similarity of two ontology terms by typically evaluating their commonness normalized to their uniqueness in terms of information contents (Harispe et al 2014) (Ranwez et al 2014). The commonness of two terms is typically evaluated by the information content of the lowest/closest common ancestor as used by Resnik (Resnik 1999), Lin (Lin 1998), Nunivers (Mazandu & Mulder 2013), relevance similarity (Schlicker et al 2006) measures; or by the information content of all common ancestors as evaluated by XGraSM (Couto & Silva 2011) and TopoICSim (Ehsani & Drabløs 2016). The uniqueness of GO terms are often evaluated by taking the average of the information content (IC) of the two terms.…”
Section: Introductionmentioning
confidence: 99%